Two new species of Metamasius Horn, 1873 (Coleoptera: Curculionidae: Dryophthorinae) from Ecuador and Colombia - Anderson, Robert S. (Zootaxa, 2021)
Two new species of South American Metamasius Horn (Coleoptera: Curculionidae: Dryophthorinae) are described: Metamasius onorei new species from Cotopaxi, Ecuador and Metamasius pilirostris new species from west of Río Yurumangui, Colombia. Diagnostic characters and images are provided for both new species to facilitate identification.